PENINGKATAN ENTREPRENEURSHIP AWARENESS DENGAN ADOPSI TEKNOLOGI INFORMASI DI LINGKUNGAN PONDOK PESANTREN - Maheni Ika Sari; Ahmad Baiquni (SEGMEN Jurnal Manajemen dan Bisnis, 2010)
Nowadays, information technology plays important role in education and business via all information technology devices. The aim of this study is to capture the level of information technology adoption in keeping with enhancement of entrepreneurship awareness among students in boarding school which is developing their curriculum and management in lately years.  Although most of boarding schools have computer, these findings indicate that generally adoption of information technology by boarding school for entrepreneurship study is still very limited, because of many internal factors, such as limited finance source, conventional paradigm and inadequate computer skill. They use this technology just for operational and opportunistic purposes. Considering that we need new entrepreneurs to increase our national economy, therefore, it is suggested that information technology on entrepreneurship subject is a must. Keywords        :           boarding school, entrepreneurship awareness, information technology.